Research on Dynamic Compression Testing of Silicone Rubber under Different Temperatures. Issue 1 (August 2021) - Zhu, Xintao; Li, Wenbin
Abstract: For study the mechanical characteristic of silicone rubber under impact loading, the Uniaxial compression tests of silicone rubber under different strain rates (1 × 10 3 /s∼6 × 10 3 /s) and temperatures (233K∼373K) were carried out with test device using the split Hopkinson pressure bar which has a controllers of temperature. The dynamic stress-strain curves and related dynamic mechanical parameters of silicone rubber were generated. The results show that the dynamic compressive strength of silicone rubber at different temperatures has the characteristics of the strain rate strengthening, which increases along with the raise in strain rate. Under dynamic condition, the stress-strain curve at 263K shows the characteristic of transition to "glass state".